RELATIONSHIP BETWEEN ENVIRONMENTAL FACTORS AND COMMUNITY BEHAVIOR WITH THE INCIDENCE OF DENGUE HEMORRHAGIC FEVER (DHF) IN THE WORKING AREA OF THE UPTD MEURAXA HEALTH CENTER, BANDA ACEH CITY - Santi, Hafnidar; Santi, Tahara Dilla; Arlianti, Nopa (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2025)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease that remains a public health concern and frequently causes outbreaks. In the working area of Meuraxa Public Health Center, DHF cases increased from 2015 to 2017 and remained relatively high in 2018. Method: This study used a case-control design with a descriptive-analytic approach. The sample consisted of 16 DHF cases and controls from the community who did not suffer from DHF, selected through total sampling. Data were collected using questionnaires and observations, then analyzed using logistic regression with Stata 13. Result: Significant associations were found between DHF incidence and temperature (p=0.003; OR=22), humidity (p=0.009; OR=4.6), knowledge (p=0.003; OR=6.8), attitude (p=0.037; OR=3.2), the habit of hanging clothes (p=0.039; OR=5.2), and mosquito larvae eradication (p=0.061; OR=3.2). Recommendation: Education and community outreach by health officers need to be enhanced to support DHF prevention through behavior and environmental management.